Platform-building by male and female Ruddy Ducks - Siegfried, W Roy (Wildfowl, 1973)
Behaviour appropriate to nest-building is relatively common in both male and female Ruddy Ducks Oxyura jamaicensis at a time preceding by 3-4 weeks, the egg-laying season in southern Manitoba, Canada. The birds spend much time resting and sleeping on these platforms at a time of the year when the water is still cold. It is suggested that the platforms are used as a means of enhancing the efficiency of thermoregulation.